Implementasi Model Pembelajaran Visual, Auditori, Dan Kinestetik Dalam Peningkatkan Motivasi Belajar Siswa Pendidikan Agama Islam Di Sekolah Menengah Atas Miftahul Ulum Rombuh Kecamatan Palengaan Kabupaten Pamekasan - Moh Ainur Rizki Ramadani; Muhammad Yahya; Alfan Elsandi; Sofia Sofia; Muhammad Hadir (Kariman: Jurnal Pendidikan Keislaman, 2023)
This study aims to describe the implementation of the Visual, Auditory, and Kinesthetic learning model in improving student learning motivation in Islamic Religious Education at Miftahul Ulum High School, Rombuh Village, Palengaan, Pamekasan, and to identify supporting and inhibiting factors in its implementation. The background of this study stems from the initial finding that the VAK learning model has been used by Islamic Religious Education teachers. However, its implementation has not been optimal, resulting in significant improvement in student learning motivation. This study used a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. Data sources included the principal, Islamic Religious Education teachers, and 10th-grade students. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results indicate that the implementation of the VAK learning model at Miftahul Ulum High School has been carried out through several stages, but has not fully followed the VAK steps. Teachers often emphasize visual and auditory aspects, while kinesthetic elements are less widely applied due to time and media limitations. Students are also unfamiliar with VAK-based learning activities, so some remain passive and lack confidence when asked to actively participate. However, the implementation of VAK has been shown to increase enthusiasm and engagement for some students, particularly when teachers use visual media and discussion activities. Supporting factors for implementing the VAK learning model include teacher creativity, school support, and the availability of basic learning resources. Inhibiting factors include limited kinesthetic support media, insufficient time allocation, and varying student abilities in adapting to active learning models. Overall, the VAK learning model has the potential to increase student learning motivation if implemented consistently, creatively, and supported by adequate learning facilities.